Utilização de três modelos de produção de carne ovina na região semi-árida do Brasil - Teixeira, Marcílio Costa (2010)
The objective of this study was to determine the reproductive performance of Santa Inês ewes maintained in three production models to determine the influence of the technological level in the reproduction of animals. During three years 150 sheep were assessed before the treatment period divided into three equal groups according to age and body weight, each group being subjected to three different production models. In Model 1, ewes were mated three times in two years, maintained in native grassland (caatinga) during the mating season (rainy season) and pasture (dry season) during the third trimester of gestation until the next mating. In Model 2, ewes were mated once a year with repeat coverage, five months after the first, kept on native pasture before, during and after the mating season (rainy season) and cultivated pasture during late gestation and lactation (dry season). In Model 3, ewes were mated once a year and kept on native pasture with supplementation in the form of hay in the dry season. All animals received mineral supplementation throughout the experimental period. Significantly influence the production model and year of observation in the body weights of the sheep at mating, calving and weaning rates and calculated, with values significantly higher than in Model 1 and in year 2008. It is concluded that the technological level has a major influence on body weight and reproductive performance of sheep in semi-arid region of Brazil, with three viable calving at two years.